EFEITO DO EXERCÍCIO ISOMÉTRICO EQUALIZADO EM DENSIDADE SOBRE AS RESPOSTAS HEMODINÂMICAS DE IDOSAS HIPERTENSAS. - LEITE, Thiago Gomes (2018)
Introduction. Isometric exercise has been shown to have great potential in reducing blood pressure, but mainly for the hypertensive elderly population, the effects of training variables, such as density, are still controversial. Objective: To compare the effects of two different isometric exercise protocols, equalized in density, on the acute cardiovascular responses of elderly hypertensive patients. Material and Method: Thirteen (13) hypertensive elderly women participated in the study, who performed two exercise protocols equalized in density. Protocol A: 4 series of 2 minutes, intensity of 30% of 1RM and interval of 2 minutes between each series (protocol A); and Protocol B which corresponded to: 16 series of 30 seconds, intensity of 30% of 1RM and interval of 24 seconds between each series. The following variables were analyzed: systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), heart rate (HR), subjective perception of effort (PSE) and nitrate and nitrite concentration. Results: An increase in SBP, MAP, FC and DP was observed at the post-momentum compared with the pre-exercise moment. In the comparison of the responses between the two protocols, a higher increase in SBP, DBP and HR was observed in protocol B. It was not possible to observe a hypotensive effect immediately after, at 1 hour and / or 24 hours after the exercise sessions. In relation to heart rate variability, in the frequency domain, the HF (High Frequency) showed a reduction after the B protocol, and in the time domain, the RMSSD presented reduction after the two protocols. The concentration of nitrite and nitrate did not change significantly after isometric exercise in any of the protocols. Conclusion: The isometric exercise of lower pause presented greater hemodynamic responses, although none of the protocols presented hypotensive effect. Factors related to metabolism such as nitrate and nitrite concentration, as well as factors related to the autonomic system did not present significant variations suggestive of hypotensive effect.